Implementasi Metode Finite State Machine pada Permainan Tradisional Setatak Berbasis Android - Agustin Agustin; Aldino Evel; Susanti Susanti; Rahmaddeni Rahmaddeni (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) STMIK Global Informatika MDP, 2021)
The growth of the game trend today tends to be mobile games.There are still a few games that introduce traditional games to the younger generation, especially for children, so there is a lack of children's knowledge about traditional games, for example, Setatak game. Setatak is a traditional game played by jumping over a box drawn on a flat surface on the ground, jumping from one box to another using only one leg. Along with advances in technology, in order to maintain and preserve traditional games, traditional games are made based on Android in 2D. The method used is the Finite State Machine (FSM) method. Finite State Machine (FSM) method, which is a control system design that describes the behavior or working principles of the system using the following three things: State, Event and action. The application of the FSM method in this game is to regulate the behavior of the system, namely the movement of the player's feet from one box to another during the game.With the existence of this game application, children can understand and be able to play game games as well. The test results show that the game can be played, liked and interested by children as well as increase children's knowledge about traditional games setatak